Study on Lighting Parameters of Audible and Visual Warning Devices Used by the Police of the Czech Republic - Hrinko, Martin; Fiserova, Svetla (Communications - Scientific letters of the University of Zilina, 2012)
In the article, the authors are concerned with the lighting parameters of audible and visual warning devices used by the Police of the Czech Republic in reaction to European legislation on this issue. The aim of this article is to explain the principle itself and the properties of radiation of light with its photometric specifications that can be evaluated and perceived by human eye, including subsequent negative effects on human health. The article presents a study of evaluation of measured values of luminance, luminous intensity and other photometric quantities of selected audible and visual warning devices used by the Police of the Czech Republic.